Potential accumulation of lead (Pb) through biomagnification In jambal catfish (Pangasius djambal) cultured in the old post mining pit lakes of Bangka Belitung archipelago - Robin Robin (Jurusan Akuakultur, Universitas Bangka Belitung, 2016)
The consequences of tin mining activities is the formation large basin-shaped holes filled with water in which the local (Bangka Belitung islands) term is a Kolong or Camuy (lake). Heavy metal concentrations are still high in all the pits and endangering human health; is the image that is in today's society so that people refused to eat the fish from or doing aquaculture activities in kolong.Pb heavy metal in the jambal catfish start found in the second month, the month of December 2011 on the kidney and meat measured 0,032 mg/kg and 0,177 mg/kg, respectively. In the third month (January 2012) Pb was found in almost every organ of jambal above safe levels for consumption, ie 15,39mg/kg in liver, and 40,56 mg/kg in the flesh.Decrease in water temperature and pH also resulted in an increase of Pb accumulation in the meats of jambal catfish, which amounted to 40,56mg/kg. During the four months of cultivation, the accumulation of heavy metals Pb that occur in every organ of observation had a significant influence to the growth rate of jambal catfish. Accumulation of Pb in each jambal catfish organs in the first and second months of cultivation is almost immeasurable but still lowering the rate of growth since the first month. The jambal catfish body already polluted with the heavy metals, as evidenced by Pb measured in the meats and kidney in the second month of cultivation.